Physiological Differences in Cardiorespiratory and Metabolic Parameters Between Football Players from Top- and Mid-Ranked Teams in the Serbian Super League - Radivoje Radakovic; Dejan Martinovic; Borko Katanic; Karuppasamy Govindasamy; Nikola Prvulovic; Vlad Adrian Geantă; Viorel Petru Ardelean (Applied Sciences)
This study investigated physiological differences in cardiorespiratory and metabolic performance parameters between professional football players from top- (TR) and mid-ranked teams (MR) in the Serbian Super League. A total of 55 male outfield players (TR: n = 29; MR: n = 26) were assessed in March 2022 using a maximal multistage treadmill protocol and lactate analysis. The key cardiorespiratory variables included maximum oxygen uptake (VO2max), heart rate at the anaerobic threshold (HR AT), and recovery heart rate metrics, while the metabolic variables focused on lactate concentrations and efficiency indices. The results indicate that the TR players achieved significantly lower HR AT values (162 ± 10.26 vs. 168.77 ± 7.28 bpm; p = 0.017) and demonstrated superior second-minute recovery (%Re 2′: 66.62 ± 14.08% vs. 34.53 ± 9.13%, p < 0.001). In contrast, the MR players exhibited higher VO2max (62.65 ± 4.48 vs. 60.06 ± 3.29 mL/kg/min; p = 0.017) and greater cardiorespiratory efficiency scores. The lactate parameters were comparable between the groups, except for the metabolic efficiency index (Index ME), which were favorable among the TR players (p = 0.011). These findings highlight that while MR players possess higher aerobic capacity, TR players demonstrate superior physiological recovery and metabolic control, reflecting adaptations to different tactical demands and match intensities. The results offer practical implications for individualized training design and performance monitoring in elite football settings.